Philflex Wires and Cable Company a quality control study - Eiaw, Sherilyn Uy; Lam, Anna Grace A.; Montanez, Mario V., II; Uy, Ofelia E. (College of Engineering, 1999)
This paper presents an Industrial Quality Control Study on Philflex Wires and Cable Company. The group aims to study and improve the existing quality system of the company through the application quality control techniques. By analyzing the present organization and system of the company enabled the group to diagnose the various problems encountered by the company's internal system. In conducting the study, investigations are done through data gathering and interviews to understand production operations and the company's quality assurance system. The research study concentrates on the level of scrap generated in the manufacture of electric wires and cables. Among primary goals are to investigate the causes of excessive scrap and to come up with several solutions to the problems. After thorough analysis of the causes and their significance, in the generation of scrap, recommendations and implementation strategy are made to address the company's excessive scrap problem.